A method to calibrate the n-γ discrimination property of scintillators in low energy region. (January 2021) - Bai, Huaiyong; Zhang, Guohui; Xiong, Zhonghua; Li, Yongming; Zhao, Deshan; Su, Ming; Mo, Zhaohong; Wang, Xiaodong; Gao, Fan; Zhang, Hongjun; Zhang, Zhenyu; Wen, Ji
Abstract: Scintillators with n - γ discrimination property are widely used in the measurement of neutrons. In sub MeV region, the n - γ discrimination property will be greatly deteriorated so that the neutron and γ -ray events can't be accurately discriminated. As a result, the determination of the proportions of neutron and γ -ray events beyond the discrimination threshold is important if scintillators are applied to measure the low energy neutrons. In the present work, a method based on the time-of-flight technique is proposed to calibrate the proportions of neutron and γ -ray events beyond the discrimination threshold. After the calibration, the numbers of the measured neutron and γ -ray events can be separately determined even if the neutron and γ -ray events can't be perfectly discriminated. Highlights: A method was proposed to calibrate the proportions of neutron and γ-ray events beyond the discrimination threshold. The numbers of the neutron and γ-ray events can be separately determined even if they can't be accurately classified. After the calibration, a lower detection threshold can be adopted to improve the detection efficiency of the scintillators.